Disrupting an Epistemology of White Ignorance through writing a Racial Autobiography - de Saxe, Jennifer Gale; Ker, Alex (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2023)
White students who enter university having few experiences engaging with race and white supremacy are likely limited in their ability to perceive and understand structural white ignorance and racial bias towards Black, Indigenous and People of Color (BIPOC). As a result, these students and their professors tend to gloss over the insidious ways that hegemonic whiteness is upheld within the university setting. Such failure to critically examine structural whiteness misses opportunities to confront an epistemology of white ignorance, the Racial Contract, and their connection to sustained racial domination. Throughout this article, we argue that students can work towards identifying and disrupting white ignorance by writing a racial autobiography that critically reflects upon students’ own experiences of race and racism. We use this assignment to illustrate what it might mean for students to ‘become’ co-conspirators within and beyond the university setting.